Comparison of different extraction methods for the analysis of volatile secondary metabolites of Lippia alba (Mill.)N.E. Brown, grown in Colombia, and evaluation of its in vitro antioxidant activity - Stashenko, E.E.; Jaramillo, B.E.; Martínez, J.R.
Hydrodistillation (HD), simultaneous distillation solvent extraction (SDE), microwave-assisted hydrodistillation (MWHD), and supercritical fluid (CO2)extraction (SFE)were employed to isolate volatile secondary metabolites from fresh leaves and stems of Colombian Lippia alba (Mill.)N.E. Brown. Kovats indices, mass spectra or standard compounds were used to identify around 40 components in the various volatile fractions. Carvone (40.57
Keywords: LIPPIA ALBA; EXTRACTION METHODS; HEADSPACE ANALYSIS; ANTIOXIDANTS; VOLATILE ORGANIC COMPOUNDS; CARVONE